Printing of hard ferromagnetic materials for remote magnetic actuation (Transactions on Additive Manufacturing Meets Medicine, 2021)
The remote magnetic actuation of untethered devices has great potential for many clinical applications such as drug targeting and precision surgery. 3D printing offers great flexibility in the manufacturing process of these milli- and micro-scale devices. To achieve better functionalization of these devices it is beneficial to directly integrate the desired properties into the printing process. This work focuses on the development and analysis of a magnetic print material. NdFeB microparticles of different concentrations were incorporated into a liquid polymer resin for LCD-based 3D printing. The print quality is investigated and the resulting magnetic properties are analyzed for their suitability to be used for remote magnetic actuation.
Keywords: magnetic actuation; magnetic printing; permanent magnets; functionalized prints